"I am Dark and Lovely": Let the Shulammite Woman Speak. Issue 3 (2nd September 2018) - Day, Keri
ABSTRACT: In this article, I not only interrogate black Pentecostal women's complex engagement with their bodies through traditional ideas of holiness but also construct more liberative ways forward in thinking about sexual desire, sexual agency, and the celebration of black women's flesh through engaging a scriptural resource, the Song of Songs . A part of the Hebrew Bible and the Christian Bible, Song of Songs introduces the reader to a woman who is "black and lovely, " who initiates sexual encounters, who roams the streets looking for her lover, who speaks openly about her sexual desires, and who does not refer to herself as married in this quest for sexual freedom and communion. Drawing on womanist biblical scholarship, this text holds eroticism within the history of God, centring black women's sexual agency. The Song of Songs offers critical theological resources that can critique and expand the present Pentecostal imagination surrounding black women's sexuality.